(3LRA ef cJGH GdGYJHGQ aj GdedchJs - (3LHQjd Hf fhM Hf CHj fhM GdGfHGQjs
(3ChdgG (B:s
(3GdMeO ddg , hef cJGH GdEYJHGQ ai GdedchJ JCdja LHQjd Hf fhM acQ ai Ndb Gddg GdRQGaI hENJdGa CYVGFgG hTHggG HCYVGA CUfGa ef GdMjhGf s
(3BNQgG (B:s
(3deG PcQ Cgd GdNHQI HeG ai ZjGV PGJ CTLGQ JMJGL Edi Whd GdYfb dJJfGhd CMQGe Jdc GdCTLGQ aJdae ef KeGQgG GfJgi HdaXI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(489(3O(B) s
Keywords: (3GdeLGejYs